Characterization of Eco-Friendly Composite Board as a Heat Insulator Based on Polypropylene Waste with Coconut Coir Filler - Medyan Riza; Sri Aprilia; Nasrullah Razali; Mukhlishien Mukhlishien; Muhammad Rabani Fikry; Hanif Saputra (Journal of Applied Technology, 2022)
Composite boards made of coconut fiber with polypropylene as a matrix are an option in dealing with environmental pollution problems caused by these materials. Coconut coir fiber has pores that can absorb heat, which is one of the global problems now. The process of making this composite is divided into 3 stages, namely the preparation stage of coco fiber into two different sizes, namely 40 and 80 mesh. The second stage is the process of preparing polypropylene into a matrix by heating the polypropylene until it melts and the desired texture is obtained. And finally, the mixing process consists of a predetermined fiber size, a polypropylene matrix (10:90, 20:80, 30:70 (%b fiber/%matrix)), and the resulting mixture is printed. The board was tested for its physical properties, namely water absorption and density, then analyzed for its mechanical properties through the fracture modulus test and analyzed the morphology structure, namely SEM and FTIR, as well as heat resistance testing through the Differential Scanning Calorimetry test and the Thermogravimetric Analyzer test. From the results of the study, it was obtained that a sample with a size of 40 mesh and a ratio of 10:90 had the best density and DSA values, namely 0.794 gr/cm3 and 2.8%. The best sample mechanical properties were obtained by a sample with a size of 80 mesh at a ratio of filler to matrix of 10:90 with an MOR value of 7.75 and an MOE of 1198 MPa. The highest melting point of the composite board was obtained in the f/m3 sample with a filler: matrix percentage of 30:70 and a coir size of 40 mesh, at a temperature of 518 oC. The highest thermal stability was obtained in the f/m6 sample with a filler and matrix percentage of 30:70, with a thermal stability temperature ranging from 290 to 533 and a mass loss of 4.26 mg.